Aspects of Gas Storage: Confined Geometry Effects on the High-Pressure Adsorption Behavior of Supercritical Fluids - Eder, Simon; Guggenberger, Patrick; Priamushko, Tatiana; Kleitz, Freddy; Thommes, Matthias (Langmuir, 2024)
During the last decades, major progress was made concerning the understanding of subcritical low-pressure adsorption of fluids like nitrogen and argon at their boiling temperatures in nanoporous materials. It was possible to understand how structural properties affect the shape of the adsorption isotherms. However, within the context of gas storage applications, supercritical high-pressure gas adsorption is important. A key feature here is that the experimentally determined surface excess adsorption isotherm may exhibit a characteristic maximum at a certain pressure. For a given temperature and adsorptive/adsorbent system, the surface excess maximum (and the corresponding adsorbed amount) is related to the storage capacity of the adsorbent. However, there is still a lack of understanding of how key textural properties such as surface area and pore size affect details of the shape of supercritical high-pressure adsorption isotherms. To address these open questions, we have performed a systematic experimental study assessing the effect of pore size/structure on the supercritical adsorption isotherms of pure fluids such as C2H4, CO2, and SF6 over a wider range of temperatures and pressures on a series of model materials exhibiting well-defined pore sizes, i.e., ordered micro- and mesoporous materials (e.g., NaY zeolite, KIT-6 silica, and MCM-48 silica). A fundamental result of our experiments is a unique fluid-independent correlation between the pressure of the surface excess maximum pmax (at a given temperature) and the pore size (by taking into account the kinetic diameter of the fluid and the underlying effective attractive fluid-wall interaction). Summarizing, our results suggest important structure-property relationships, allowing one to determine, for given thermodynamic conditions, important information related to the optimal operating conditions for supercritical adsorption applications. The insights may also serve as a basis for optimizing and tailoring the properties of nanoporous adsorbent materials for gas storage applications.
CRIS-Team Scopus Importer:2024-02-23